COVID-19: Need of the hour to revisit asymptomatic prevalence of coronavirus pandemic - Richard Avoi; Syed Sharizman Syed Abdul Rahim; Mohammad Saffree Jeffree; Pasupuleti Visweswara Rao (2020)
Since the Coronavirus disease 2019 (COVID-19) pandemic unfolded in China (Huang et al., 2020) back in December 2019, thus far, more than five million people were infected with the virus and 333,401 death were recorded worldwide (WHO, 2020b). The exponential increase in number shows that COVID-19 spreads faster compared to Severe Acute Respiratory Syndrome (SARS) or Middle East Respiratory Syndrome (MERS). A study (Zou et al., 2020) has shown that high viral loads of Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are detected in symptomatic patients soon after the onset of symptoms, wherein the load content is higher in their nose than in their throat. Furthermore, the same study has revealed similar viral loads between symptomatic and asymptomatic patients. Therefore, these findings may suggest the possibility of COVID-19 transmission earlier before the onset of symptoms itself. In the early stages of the pandemic, the control measures carried out have focused on screening of symptomatic person; at the time, the whole world thought that the spread of SARS-Cov-2 would only occur through symptomatic person-to-person transmission. In comparison, transmission in SARS would happen after the onset of illness, whereby the viral loads in the respiratory tract peaked around ten days after the development of symptoms by patients (Peiris et al., 2003). However, case detection for SARS (i.e. screening of symptomatic persons) will be grossly inadequate for the current COVID-19 pandemic, thus requiring different strategies to detect those infected with SARS-CoV-2 before they develop the symptoms.